Compllete handyman do-it-yourself encyclopedia : a complilation of special interest projects and manual for the repair and care of homes, autos, appliances, hobby equiipment. XIX.tools-upholstery (H.S. Stuttman Co, 1975)
2.779-2.932 p.; 25 cm.